Falling in with the wrong crowd: linkage in the age of populism. Issue 1 (2nd January 2019) - Margulies, Ben
ABSTRACT: The article examines the role of linkage in Viktor Orbán's Hungary, where liberal democratic institutions and practices have eroded since 2010. Levitsky and Way (2010, Competitive authoritarianism: hybrid regimes after the Cold War, New York: Cambridge University Press) provided a definition of linkage, and theorized an important role for these links in the democratization process. However, there has been less examination of how linkages affect the quality of existing democracies. Looking at the case of Hungary, I formulate hypotheses about the role of linkage and maintaining the quality of democracy. I propose that links that may encourage democratization have proven too weak to sustain democratic quality in the face of illiberal, populist challenges. I also argue that new linkage patterns have been forming with tend to degrade democratic quality, specifically between populist parties in Hungary and those in other parts of Europe; and between Hungarian parties and various institutions, including parties and the state, in Russia. The paper hopes to use the linkage model to inform developments in the literature on democratic regression and democratic quality.